The Importance of Inhaler Adherence to Prevent COPD Exacerbations - Jardim, Jose R. (Med Sci (Basel), 2019)
It has been shown that the better outcomes of chronic obstructive pulmonary disease (COPD) are closely associated with adherence to drug therapy, independent of the treatment administered. The clinical trial Towards a Revolution in COPD Health (TORCH) study clearly showed in a three year follow up that patients with good adherence to their inhaler treatment presented a longer time before the first exacerbation, a lower susceptibility to exacerbation and lower all-cause mortality. The Latin American Study of 24-h Symptoms in Chronic Obstructive Pulmonary Disease (LASSYC), a real-life study, evaluated the self-reported inhaler adherence in COPD patients in seven countries in a cross-sectional non-interventional study and found that approximately 50% of the patients had good adherence, 30% moderate adherence and 20% poor adherence. Adherence to inhaler may be evaluated by the specific inhaler adherence questionnaire, the Test of Adherence to Inhalers (TAI). Several factors may predict the incorrect use of inhalers or adherence in COPD outpatient, including the number of devices and the daily dosing frequency. Ideally, patient education, simplicity of the device operation, the use of just one device for multiple medications and the best adaptation of the patient to the inhaler should guide the physician in prescribing the device.